Respuesta :
To get from one even number to the next even number you have to add 2.
Ex. 4, 6, 8. If I start with 4, I have to add 2 to 4 to get to 6, and add 4 to 4 to get to 8. Since we don't know the starting point in this word problem we start with'x' and add 2 and add 4.
x = (x + 2) + (x + 4)
x = 2x + 6
The first equation
Ex. 4, 6, 8. If I start with 4, I have to add 2 to 4 to get to 6, and add 4 to 4 to get to 8. Since we don't know the starting point in this word problem we start with'x' and add 2 and add 4.
x = (x + 2) + (x + 4)
x = 2x + 6
The first equation
Answer:
Step-by-step explanation:
Given that the smallest number of three consecutive even integers is equal to x.
The next two even integers would be x+2 and x+4
Sum = [tex]x+2+x+4 =2x+6[/tex]
This equals first number x
Since these two are equa,
[tex]x=2x+6[/tex]
Hence I option is right.